Reliability of Online Surveys in Investigating Perceptions and Impressions of Faces - Hirao, Naoyasu; Koizumi, Koyo; Ikeda, Hanako; Ohira, Hideki (Frontiers in Psychology, 2021)
Online experimental methods are used in psychological studies investigating the perceptions and impressions of facial photographs, even without substantial evidence supporting their reliability and validity. Although, the quality of visual stimuli is more difficult to control remotely, the methods might allow us to obtain a large amount of data. Then the statistical analysis of a larger volume of data may reduce errors and suggest significant difference in the stimuli. Therefore, we analyzed the reliability and validity of online surveys in investigating the perceptions (shine, red, and dark) and impressions (attractiveness, trustworthy, and so on) of facial photographs created from averaged faces with skin tones modified using computer graphics (CG). In this study, we conducted online (Online1) and laboratory experiments with well-controlled conditions (Control). For each experiment, 50 participants (men and women in Japan, age: 20–59years) completed the same questionnaire regarding their impressions of the same 28 CG facial photographs. The results showed significant correlations between the two experiments for all 19 items in the questionnaire. SD in the Online1 compared to the Control from the stimuli and individual differences were 56–84 and 88–104% in each questionnaire items, respectively. Moreover, the rates of mismatching perceptual evaluations to the corresponding physical features demonstrated in the photographs were 4.9–9.7% on average in an additional online survey of another 2,000 participants (Online2). These results suggest that online surveys can be applied to experiments to investigate impressions from CG facial photographs instead of general laboratory experiment by obtaining an appropriate number of participants to offset larger statistical errors that may result from the increased noise in the data from conducting the experiment online.